Chemical, nutritional, anti-nutritional, and technological profile of bacaba fractions (Oenocarpus bacaba Mart.): Promising fruit from the Brazilian legal Amazon - ALVES, Vânia Maria; AMORIM, Katiúcia Alves; ASQUIERI, Eduardo Ramirez; ARAÚJO, Elias da Silva; SOUZA, Adriana Regia Marques de; MELO, Adriane Alexandre Machado; MURADIM, Lídia Bicudo de Almeida; DAMIANI, Clarissa (Food Science and Technology, 2025)
Bacaba belongs to the same family as açaí, and its pulp is consumed by the local population of the Brazilian Amazon region. The aim of this study was to characterize the peel+pulp and seed fraction, and the peel+pulp flour and seed flour, seeking to provide the agro-industrial market with an alternative for exotic fruit consumption, collaborating with the whole consumption of foods. The results showed that all fractions contain amounts of total fiber above 20 g/100 g, lipid contents that vary according to the fraction, highlighting the values of some minerals. Bioactive compounds such as epicatechin, procyanidin A2, biochanin A, myricetin, and kaempferol were found in the peel+pulp, seed, and its flour; the flour from the husk+pulp fraction has good solubility in milk; the seed is a source of carbohydrates; and the seed flour has a high antioxidant capacity. We conclude that bacaba fractions can be applied in food products, mainly in the form of flour, adding nutritional value and contributing to the demand for the full use of the fruits.